ANALISIS KEBIJAKAN COUNTER-RADIKALISME MELALUI FORUM KERUKUNAN UMAT BERAGAMA (Studi Deskriptif tentang Peran FKUB dalam Rangka Mencegah Lahirnya Gerakan Radikal di Kabupaten Tasikmalaya ) - Ray Adhari Jajuri, - (2021)
The phenomenon of radicalism became a sensitive issue in the discussions later this decade, policies focused in prevention areas at the District level integrated into the program of the establishment of the Forum Religious Harmony. The central role of FKUB includes the prevention and countermeasures of radicalism movements, as well as analyzing movements that can lead to radical actions. So this is the basis of researchers to examine the policy of counter-radicalism in Tasikmalaya through the establishment and running of FKUB programs that are considered very central in counter-radicalism. The purpose of this study in general is to analyze the application of counter-radicalism policy applied by the Tasikmalaya District Government through the Forum Religious Harmony Tasikmalaya Regency. The method used in this study is the case study method. Then with this method, the analysis of counter-radicalism strategy applied by tasikmalaya district government through the Forum Religious Harmony Tasikmalaya regency as a situation or event. The results showed; Radical movements that arise do not form terrorism networks, but in the form of conflicts; Tasikmalaya district in combating radicalism movement through FKUB, Kesbang Linmas, army and police; FKUB Tasikmalaya district collaborates with various institutions to produce programs that play a role to conduct dialogue in an effort to prevent conflicts that lead to radical movements; Strategies used with the approach of Soft Power Aproach and Hard Power Aproach; FKUB programs that has been running certainly reaped the results of radical movement groups that can immediately be muted existence with various handling and cooperation with related institutions.